Current understanding of the cardiotoxicity-related treatment of immune checkpoint inhibitors in breast cancer - Jiajing Dai (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2023)
Immune Checkpoint Inhibitors (ICIs) as the most important and widely used currently, have changed the traditional approach to cancer treatment and significantly improved the prognosis of most patients with advanced malignancies. Breast cancer is the most dangerous threatening tumor to women's health and life globally, ICIs have shed light on the treatment for refractory breast cancer subtypes, including Triple-Negative Breast Cancer (TNBC) and trastuzumab resistance of human epidermal growth factor receptor 2 positives (HER2+). However, immune-related adverse events (irAE) associated with ICIs bring many extra considerations. Among these, potential cardiotoxicity is rarely seen but with the highest fatality rate. In the present review, we introduced the ICIs approved for the treatment of breast cancer and brief guideline for clinical application. Then we briefly summarized ICIs-related cardiotoxicity in breast cancer and mechanism based on immunology and basic medical research. Furthermore, we make a brief summary of the diagnosis methods.